PENERAPAN METODE COOPERATIVE LEARNING TIPE BERPASANGAN UNTUK MENINGKATKAN KEMAMPUAN TEKNIK DASAR BERMAIN KASTI DI KELAS V.A SDN 002 PANTAI CERMIN KABUPATEN KAMPAR - Abd. Mulud (JURNAL PAJAR (Pendidikan dan Pengajaran), 2018)
This research is motivated by the low ability of basic technique of playing the students' grate V.A SDN 002Pantai Cermin Kabupaten Kampar. This study aims to improve the basic techniques of playing kasti throughcooperative learning methods paired type students class V.A SDN 002 Pantai Cermin Kampar District. Thesubjects of this study are students of class V.A SDN 002 Pantai Cermin Kabupaten Kampar with the number ofstudents as many as 28 people. The form of research is classroom action research. The instrument of thisresearch consisted of performance instrument and data collection instrument in the form of observation sheet ofteacher activity and student activity. The basic technique ability to play with cooperative method of paired typelearning in VA VAN 002 Pantai Cermin Kabupaten Kabupaten Kampar average of basic technique ability toplay the students' census on the initial test is categorized less with percentage 48,9%, in cycle I increase to68,4% with sufficient category whereas in cycle II the average ability of students is categorized very high with90.8% percentage. The cassical completeness specified in this study that 80% of students have been declaredthoroughly achieved. The conclusion of this research is the application of cooperative learning method pair typecan improve basic technique of playing kasti.